2022
DOI: 10.1002/vetr.1794
|View full text |Cite
|
Sign up to set email alerts
|

Sex disparity in oronasal presentations of canine transmissible venereal tumour

Abstract: Background:The canine transmissible venereal tumour (CTVT) is a contagious cancer spread by the direct transfer of living cancer cells. CTVT usually spreads during mating, manifesting as genital tumours. However, oronasal CTVT is also occasionally observed, and presumably arises through oronasal contact with genital CTVT tumours during sniffing and licking. Methods: Given that sniffing and licking transmission behaviours may differ between sexes, we investigated whether oronasal CTVT shows sex disparity. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It was also observed that occasionally, mast cell granules may not stain with Diff–Quik stain there by making the identification of mast cells difficult; in case granules were not seen, but round cells were found to be associated with an eosinophilic infiltrate, then a MCT may be suspected. 7 In cases of CTVT, PCR‐based assays for myc gene yielded better results 8 …”
Section: Differential Diagnosismentioning
confidence: 99%
“…It was also observed that occasionally, mast cell granules may not stain with Diff–Quik stain there by making the identification of mast cells difficult; in case granules were not seen, but round cells were found to be associated with an eosinophilic infiltrate, then a MCT may be suspected. 7 In cases of CTVT, PCR‐based assays for myc gene yielded better results 8 …”
Section: Differential Diagnosismentioning
confidence: 99%